2000
DOI: 10.1139/cjc-78-4-516
|View full text |Cite
|
Sign up to set email alerts
|

Reductive deposition of Au<sup>3+</sup>(aq) on o×idized silicon surfaces

Abstract: X-ray photoelectron spectroscopy (XPS) is used to determine the oxidation state of gold deposited from an aqueous solution of AuCl 4 -on to various oxidized surfaces of silicon. Although the observed Au4f signal decreased with the thickness of the oxide layer, the oxidation state of Au was determined as 0 for all the samples analyzed. From the angular dependence of the Si2p and Au4f signals it was determined that Au is deposited on top of the oxidized surfaces of metallic silicon. It is postulated that from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The Au film is stable against repeated washing with various aqueous and organic solvents. Similar results were observed by Suzer and Dag 4 X-ray photoelectron spectra of Si and SiO 2 wafers treated with HAuCl 4 for 10 h. The XPS spectrum of the Si wafer shows significant Au deposition, whereas the XPS spectrum of the SiO 2 wafer shows no evidence of Au deposition. …”
supporting
confidence: 82%
“…The Au film is stable against repeated washing with various aqueous and organic solvents. Similar results were observed by Suzer and Dag 4 X-ray photoelectron spectra of Si and SiO 2 wafers treated with HAuCl 4 for 10 h. The XPS spectrum of the Si wafer shows significant Au deposition, whereas the XPS spectrum of the SiO 2 wafer shows no evidence of Au deposition. …”
supporting
confidence: 82%
“…Therein, the activated carbon surfaces containing basic oxygen-based functional groups displayed reductive sorption of [AuCl 4 ] - via electrochemical mechanisms, while acidic oxygen-based functional groups displayed chemical reduction mechanisms . Suzer and Dag have also reported that [AuCl 4 ] - can undergo reductive deposition to Au(0) from aqueous solution at any surface which can provide an active adsorption site . Therefore, in the present case, it is probable that the reductive sorption of [AuCl 4 ] - occurs at surface defects or impurities in the GC electrode, with protons either activating these sites or otherwise facilitating the reduction process of [AuCl 4 ] - in the IL.…”
Section: Resultsmentioning
confidence: 70%
“…Examples of thin, well adhering nanoparticle films prepared via immersion of Ge(100) and metal substrates into dilute, aqueous solutions of AuCl 4 - , PdCl 4 2- , or PtCl 4 2- salts are shown in Figure . Deposition proceeds via galvanic displacement in the absence of fluoride, pH buffers, complexing agents, or external reducing agents, in contrast to earlier work. Patterning of these particle film assemblies is essential for their subsequent incorporation into higher order architectures and devices. ,
1 SEM images of (a) an Au nanoparticle film deposited spontaneously in 90 min on a Ge(100) surface from a 1 mM aqueous AuCl 4 - solution; (b) Pd and (c) Pt on a Ge(100) surface, formed from aqueous 1 mM PdCl 4 2- and PtCl 4 2- for 120 min; Pt films on (d) Zn and (e) Cu foils utilizing an aqueous 20 mM PtCl 4 2- solution for 10 s; (f) Pt on Sn foil deposited from a 20 mM PtCl 4 2- solution for 5 min.
…”
mentioning
confidence: 99%